Управление назначением длин волн световым маршрутам в сетях DWDM - Агеев, Д. В.; Переверзев, А. А. (ХНУРЭ, 2011)
The technology of wavelength division multiplexing provides the most scalable and cost effective way to increase the capacity of fiber-optic channels than technology that does not use multiplexing streams of fiber-optic channels. In addition to the methods described above, there is a method for solving RWA based on the use of optical converters, they can be used to change the wavelength of the light route, thus greatly increasing network capacity, but the cost of build ing such a network is also growing. The proposed method takes into account the distribution of wavelengths FWM nonlinear phenomenon by introducing additional constraints: the total input power, the use of the frequency plan with a distance between the frequencies of wavelengths
Keywords: мультисервисные телекоммуникационые системы; объем трафика